Actinic keratosis area and severity index (AKASI) is associated with the incidence of squamous cell carcinoma. (18th December 2017) - Schmitz, L.; Gambichler, T.; Gupta, G.; Stücker, M.; Dirschka, T.
Abstract: Background: Actinic keratoses (AKs) are commonly diagnosed clinically. Actinic keratosis area and severity index (AKASI) is a new easy‐to‐use tool to assess the severity of AKs on the head. Objectives: To determine the association between chronically UV‐induced tumours such as basal cell carcinomas (BCC) or squamous cell carcinomas (SCC) and AKASI. Methods: We performed a retrospective analysis of patients who had undergone oncological surgery due to UV‐induced tumours and who were assessed for AKASI and Physician's global assessment (PGA) prior to surgery. Statistical analysis was performed to evaluate correlation between AKASI, PGA and invasive carcinomas. Results: Of the 210 patients included, 26 patients had histologically diagnosed SCCs and presented with a median (range) AKASI of 6.9 (0–13.0) and PGA of 2 (0–4). In contrast, the 82 patients with BCCs showed a median (range) AKASI of 3.3 (0–15.2) and PGA of 1 (0–4). The Mann–Whitney U ‐test showed significant differences ( P  = 0.0018) between AKASI of patients with SCC and BCC. In addition, we found a significantly higher AKASI in patients with SCC compared to patients with non‐invasive lesions like AK and Bowen disease (BD) ( P  = 0.0275). Spearman's coefficient of rank correlation between AKASI and PGA indicates that these measures of AK severity were strongly correlated ( P  < 0.0001; r  = 0.90; 95% CI 0.865–0.920). Conclusions: Patients with SCC show significantly higher AKASI than patients with BCC or patients without invasive tumours. Hence, AKASI may be used to stratify risk for developing invasive SCC.